PENGARUH JENIS SUBSTRAT TERHADAP PERTUMBUHAN DAN PERKEMBANGAN MISELUIM BIBIT F1 JAMUR TIRAM (Pleurotus ostreatus) - M, Hatta,; A, Rahman. A.; M, Alfarisy. Y. (Percetakan Umi Toaha Makassar, 2025)
This research aims to determine how various seed media compare to the mycelium growth of F1 white oyster mushroom seeds. This research was carried out in July-August 2024, at the UMKM Cicoro Farm (Bulurokeng Oyster Mushrooms) Kel. Bulurokeng District. Biringkanaya Makassar City Prov. South Sulawesi. The experimental design used was a Completely Randomized Design (CRD) with five treatments, four replications, Corn, White Sorghum, Rice Grain, Corn + Rice Grain and Sorghum + Rice Grain. This research shows that the White Sorghum planting medium provides the best results for mycelium growth and development.